PROMOTING MENTAL HEALTH BEHAVIOR IN WOMEN OF REPRODUCTIVE AGE THROUGH ANALYSIS OF ITS INFLUENCING FACTORS IN PENIWEN VILLAGE, MALANG REGENCY - Silitonga, Hanna Tabita Hasianna; Wartiningsih, Minarni; Juliasih, Ni Njoman; Tari Kupula, Tiara; Justine Thiotansen , Keith; Cahyono, Agung; Alya Rachmanita, Fathiya; Dyah Saputri, Arini; Fathoni Syahda , Almer; Yuniati, Evi (Jurnal Biometrika dan Kependudukan, 2025)
The aims of this research is to evaluate the mental health status of women of reproductive age in Peniwen Village, Malang Regency, and to analyze factors that influence stress, anxiety, and depression, with the goal of promoting positive mental health behaviors. This research employed a quantitative, cross-sectional approac. There were 47 respondents involved in this research that accidentaly attended the local posyandu (integrated health post). Data were collected through structured questionnaires contains socio-demographic characteristics, the Depression, Anxiety, and Stress Scale (DASS-21), and perceived social support. The bivariate analysis was using chi-square and linear regression tests, while multivariate analysis was using multiple linear regression. Findings revealed that the prevalence of stress among the respondents was 10.6%, anxiety was 2.1%, and depression  was 6.4%. From bivariate analysis, it was found that occcupation was significantly associated with anxiety (p=0.012), marital status also had significant relationships with both stress (p=0.002) and depression (p=0.000). Social support demonstrated a negative and significant influence on depression (t = -1.744; p= 0.088). Multivariate analysis showed that occupation, marital status, and social support were significant predictors of depression; age and social support were significant predictors of anxiety; and marital status significantly influenced stress levels. These results showed that occupational conditions, marital status, age, and social support had critical role in shaping mental health outcomes among women of reproductive age. Enhancing mental well-being and foster healthier behaviors in this population could be done by addressing these factors through targeted community-based interventions.